2001
DOI: 10.1114/1.1342054
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Biomechanical Adaptation of the Rat Carotid to Acute Hypertension: Contribution of Smooth Muscle

Abstract: The biomechanical adaptation of the arterial wall to hypertension has been studied extensively in recent years; however, the exact biomechanical contribution of vascular smooth muscle cells (VSMCs) during the adaptation process in conduit vessels is not known. We induced hypertension in 8 wk old Wistar rats by total ligation of the aorta between the two kidneys. Mean blood pressure increased from 92 +/- 2 (mean +/- SE) mm Hg to approximately 150 mmHg. Rats were sacrificed 2, 4, and 8 d after surgery and the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0
10

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 31 publications
3
49
0
10
Order By: Relevance
“…For example, Matsumoto and Hayashi (26,27) have demonstrated in the rat with induced Goldblatt hypertension that the aortic hoop stress at in vivo pressure was rapidly returned to a physiologically normal level, i.e., within 2 wk after the induction of hypertension and remained at the level, thereafter, and that the elastic modulus of wall at the in vivo pressure became a normal value after a relatively long period of time, i.e., at 16 wk after the induction of hypertension. In addition, Fridez et al (8,9) have shown in a rat model with abdominal aortic ligation that the vascular smooth muscle cell, which is the sensing and effecting element of the adaptation process, is activated during the early phase of arterial adaptation to hypertension. Furthermore, there are many studies showing that arteries change the internal diameter in response to blood flow change keeping wall shear stress at normal, constant levels if the flow change is within a certain range (for example see Refs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Matsumoto and Hayashi (26,27) have demonstrated in the rat with induced Goldblatt hypertension that the aortic hoop stress at in vivo pressure was rapidly returned to a physiologically normal level, i.e., within 2 wk after the induction of hypertension and remained at the level, thereafter, and that the elastic modulus of wall at the in vivo pressure became a normal value after a relatively long period of time, i.e., at 16 wk after the induction of hypertension. In addition, Fridez et al (8,9) have shown in a rat model with abdominal aortic ligation that the vascular smooth muscle cell, which is the sensing and effecting element of the adaptation process, is activated during the early phase of arterial adaptation to hypertension. Furthermore, there are many studies showing that arteries change the internal diameter in response to blood flow change keeping wall shear stress at normal, constant levels if the flow change is within a certain range (for example see Refs.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that vascular smooth muscle cells (8,21,37) and endothelial cells (22,49) play important roles in the control of wall hoop stress and wall shear stress, respectively. On one hand, there are many studies on the response of in vitro cultured cells to stress, which have indicated that stress affects the proliferation and function of vascular smooth muscle cells (46,48) and endothelial cells (14,45,47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A rapid increase in intravascular pressure in animals (equivalent to the recipient twin) results in vascular smooth muscle contraction and increased resistance and medial thickness. Over a month, as the smooth muscle tone returns to normal, this increased medial thickness is maintained by remodeling 23 to preserve a constant wall stress. These changes imply that the recipient twin exposed to an acute transfusional load should have increased PWV (as seen in 1 recipient of the 3, with an acute intertransfusional process in group 1).…”
Section: Discussionmentioning
confidence: 99%
“…The vascular response to hypertension in the adult human is that of an increase in the diameter of the artery, reduced compliance and an increase in pulse pressure to reduce wall stress. Evidence from animal studies suggests that the immediate response to a rapid increase in intravascular pressure is dominated by a change in vascular smooth muscle contractile state and that over a period of a week this increased resistance is maintained by remodelling (Fridez et al, 2001). These adaptive changes remain when blood pressure is reduced experimentally in animal experiments.…”
Section: Figurementioning
confidence: 99%